Pathogenesis of gall-rust disease on Falcataria moluccana in areas affected by Mount Merapi eruption in Indonesia - S. Rahayu; Widiyatno Widiyatno; Dwi Tyaningsih Adriyanti (Society for Indonesian Biodiversity, 2020)
Abstract. Rahayu S, Widiyatno, Adriyanti DT. 2020. Pathogenesis of gall-rust disease on Falcataria moluccana in areas affected by Mount Merapi eruption in Indonesia. Biodiversitas 21: 1310-1315. The gall rust pathogen Uromycladium falcatarium affects the fast-growing tree species Falcataria moluccana (Sengon) from seedling to mature stage producing galls on all its parts. Severe infestation causes tree mortality. There were two eruptions of the volcano at Mount Merapi, Java, Indonesia during October-November 2010 near to which Sengon is grown under community forests. This study, conducted in 2014, examined the implications of the volcanic eruptions on the incidence and severity of gall rust disease on Sengon trees growing in areas affected by the eruption. It revealed that the percentage infestation on seedlings caused by teliospores of U. falcatarium collected from areas close to Mount Merapi (3-7 km away-risky area) was significantly higher compared to those collected from trees 7.1-11 (are under alert) and 11.1-15 km (area under threat) away. The teilospores and galls collected from the ‘risky area’ also exhibited morphological variations. The gall rust incidence on different parts of the tree was significantly higher in the ‘risky’ area compared to trees growing in other areas. The incidence of the disease was close to 100% in the risky area but less than 80% in areas ‘under alert and under threat’. Overall, the data indicated that the incidence and severity of gall rust disease was significantly higher in areas close to the Mount Merapi apparently due to increased virulence of the pathogen and increased susceptibility of the trees due to damges caused by the eruption. Conducive environmental conditions such as high relative humidity and temperature in the area may also have favoured this situation. Artifical inoculations using teliospores collected from infected trees in the risky area, area under alert and under threat caused severe infection on seedlings.